Thematic Interpretation Method: The Emergence of Urgency, Steps, and Characteristics: Metode Tafsir Maudhui: Kemunculan Urgensi Langkah dan Karakteristik - Hawary Anshorulloh Ash-Shiddiq; Yabqiah Rahmi (Tunas Harapan Ummat Foundation, 2024)
The Qur'an as a source to teach and guide life as hudan li al-nās (guidance for humans) which remains valid along with the challenges of an ever-growing and complex era, on the other hand, humans with various mobility feel narrow but need the guidance of the quran, especially for the problems they face in the Middle This research largely uses qualitative methods where the type of research is literature (library research). The research results of this paper that the maudhu'i method of interpretation is a method that is favored and suggested by modern mufassirs is the maudhu'i method which discusses the main themes in a letter or certain verses. This method seeks to find answers to the Qur'an by collecting verses of the Qur'an that have one purpose to discuss a particular title/topic, focusing on it according to the time of its revelation and the causes of its revelation. The advantages of maudhu'i explanation are that it answers the challenges of the times, practical, systematic, dynamic and fully understood. While the weaknesses of maudhu'i explanation are pieces of verses of the Qur'an from its order and limit its understanding according to its subject. This research is expected to provide great benefits for the study of the Qur'an